Pengaruh Modal, Harga Dan Volume Penjualan Terhadap Pendapatan Pedagang Pengecer Kelapa Di Pasar Langsa Kota - Supristiwendi; Indah Wardani; Rini Mastuti (Jurnal Penelitian Agrisamudra, 2019)
The coconut retailer run the business to get a worth profit to fulfill their family needs and develop their business also. This research used a survey method. To define the sample used ad full sampling. The coconut retailer sample was 29 person and analyzed used multiple linear regression. The result showed that stock, price and selling volume effected the coconut retailer profit in Langsa City Market.